2015
DOI: 10.1016/j.pec.2015.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Behavior determinants among cardiac rehabilitation patients receiving educational interventions: An application of the health action process approach

Abstract: Educational curricula should be designed to not only increase patients' knowledge, but also enhance intentions, self-efficacy, and action planning.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 52 publications
(61 reference statements)
1
25
1
3
Order By: Relevance
“…The empirically validated English version 16 , 17 has been translated and culturally adapted to Brazilian Portuguese. Clinicians and patients have reviewed the material, and a plain language and clear design review was completed in preparation for this trial.…”
Section: Methodsmentioning
confidence: 99%
“…The empirically validated English version 16 , 17 has been translated and culturally adapted to Brazilian Portuguese. Clinicians and patients have reviewed the material, and a plain language and clear design review was completed in preparation for this trial.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, in the cases of considering the two plannings separately, the discrepant results have been reported in different studies (e.g. no direct relation between them in Ghisi et al (2015)). Therefore, the relationship between action planning and coping planning may need to be further explored from a moderation perspective.…”
Section: Structural Modelmentioning
confidence: 91%
“…Studies have shown that using theory in crafting questionnaires and interventions can lead to more powerful assessments and effects. 25 Thus, pilot studies are key components in the process of developing instruments and used to evaluate how a sample of people from the survey population responds to the questionnaire. 48 The study was also classified as ''fair'' based on the methodological quality assessment.…”
Section: The Most Applicable Questionnaire To Assess Knowledge Of Hf mentioning
confidence: 99%
“…22 In order to plan and deliver an effective educational intervention, it is important to have precise information of what HF patients know about their condition, although better knowledge does not translate directly to behavior change. 8,11,25 In this context, the use of valid instruments to assess patients' knowledge with regard to their disease is important. It is also important for clinicians to have information about what instruments are suitable for assessing educational interventions they use in practice to improve the knowledge of their HF patients.…”
mentioning
confidence: 99%